2016
DOI: 10.1093/heapol/czw076
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SMS reminder messages for altering treatment adherence and health seeking perceptions among malaria care-seekers in Nigeria

Abstract: In Nigeria, access to malaria diagnostics may be expanded if drug retailers were allowed to administer malaria rapid diagnostic tests (RDTs). A 2012 pilot intervention showed that short message service (SMS) reminder messages could boost treatment adherence to RDT results by 10–14% points. This study aimed to replicate the SMS intervention in a different population, and additionally test the effect of an expanded message about anticipated RDT access policy change on customers’ acceptability for drug retailers’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…No existing literature has described the correlation between caregiver exposure to SBCC campaign messages and caregivers seeking care at a health facility or their children receiving prompt ACT treatment in Liberia. Research has suggested that SBCC program exposure is associated with many malaria-related health behaviors, such as mosquito net use [ 11 , 12 ] and anti-malarial treatment adherence in adults [ 13 ] elsewhere in sub-Saharan Africa. However, studies from this region have offered mixed evidence as to whether SBCC programs are positively associated with a caregiver’s care-seeking behaviors for child fever [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…No existing literature has described the correlation between caregiver exposure to SBCC campaign messages and caregivers seeking care at a health facility or their children receiving prompt ACT treatment in Liberia. Research has suggested that SBCC program exposure is associated with many malaria-related health behaviors, such as mosquito net use [ 11 , 12 ] and anti-malarial treatment adherence in adults [ 13 ] elsewhere in sub-Saharan Africa. However, studies from this region have offered mixed evidence as to whether SBCC programs are positively associated with a caregiver’s care-seeking behaviors for child fever [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the available evidence on ACT adherence is limited by variation in study designs and outcomes, differences in drug regimens, and lack of comparative studies [ 3 ]. In prior randomized trials, adherence to AL has ranged from 64 to 99% [ 33 38 ]. Similarly, adherence to co-packaged AQ + AS and AQAS has varied widely in prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not mean that they had heard of the benefit and necessity of the introduction of RDT/ACT from health professionals. To increase the demand for utilization of RDT/ACT, active promotion of its importance to villagers through mass media and/or short message service may be helpful ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%